Development of Learning Media Assisted By Articulate Storyline 3 Application On The Classification of Living Things with A Scientific Approach At Junior High School 2 Panti - Burhanudin, Agus; Khusnah, Laila; Syväjärvi, Mikael (Islamic Journal of Integrated Science Education (IJISE), 2025)
Research this aiming for develop and describe validity as well as practicality of learning media based on Articulate Storyline 3 in the material classification creature life with approach scientific at Junior High School 2 Panti. Research using the 4D development model to stage distribution limited. Products validated by experts materials, media, language, and practitioners, then tested its practicality through trial scale small (10 students) class VIII) and scale large (32 students) class VII). The validation results show a very high level of validity with average scores from each validator: subject matter experts scored 95.31%, media experts scored 96.25%, language experts scored 100%, and practitioners scored 100%. Furthermore, the practicality test results showed a score of 88.75% in the small-scale test and 91.07% in the large-scale test, which falls into the “very practical” category. With thus, the learning media developed stated to be very valid and practical for used in science learning.